If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11=g+75/10
We move all terms to the left:
11-(g+75/10)=0
We add all the numbers together, and all the variables
-(+g+75/10)+11=0
We get rid of parentheses
-g+11-75/10=0
We multiply all the terms by the denominator
-g*10-75+11*10=0
We add all the numbers together, and all the variables
-g*10+35=0
Wy multiply elements
-10g+35=0
We move all terms containing g to the left, all other terms to the right
-10g=-35
g=-35/-10
g=3+1/2
| 6a+12=a-87 | | 9(z-846)=711 | | 3=q/10-18 | | -4k+28=4 | | r/11+222=253 | | 33=-2v+45 | | 53=10y+3 | | 100-79k=79 | | 4x-36=3x-5x | | y/10-3=8 | | -7=2+v | | 24=-4b-12 | | 45/k=5 | | 5x+3x+(2x+20)=180 | | 7=42/g | | 2+2w+3.5=58 | | x-5/12=8 | | 8y+y^2=200 | | 5=40/p | | 3x+14=299 | | 6x+15x-38=-10x-16 | | 6x/7-2x21=25/21 | | 10=50/c | | Y=1.3x-1.9 | | m+16-2m+3m=4-24+16 | | 53-k=38 | | -1x+270=-2x-100 | | 7j+1=99 | | 72/s=9 | | 61-z=28 | | 61−z=28 | | k/6+86=94 |